Rancang Bangun Aplikasi Pengadaan Barang Berbasis Web dengan Fitur Approval Workflow pada Unit Karya YPAC Jakarta - M. Fachriz Azis Wantah; Farizi Ilham; Rafi Hibban Hafizh; M. Rivaldi Saptawiguna (CV. Shofanah Media Berkah, 2026)
Unit Karya YPAC Jakarta is a platform for people with disabilities to develop their creativity and produce various economically valuable products. In its operations, the procurement process for goods such as raw materials and equipment is still carried out manually, which often leads to delays, lack of transparency, and difficulties in recording and tracking item requests. The absence of a structured approval flow also makes the procurement process less effective and prone to errors. This study aims to design a web-based procurement application equipped with an approval workflow feature. The system was developed using PHP, MySQL, and XAMPP through the stages of requirements analysis, design, implementation, and testing. The main features built include an item request form, a tiered approval flow, notifications, as well as request history and tracking. Black Box testing of 12 scenarios showed that all functions worked as expected. The results show that the system can improve efficiency, minimize errors, and provide transparency at every stage of the process, thus supporting the operational activities of Unit Karya YPAC Jakarta to be more effective and well-structured.